KAJIAN PEMODELAN DERET WAKTU: METODE VARIASI KALENDER YANG DIPENGARUHI OLEH EFEK VARIASI LIBURAN - Winda Triyani; Rina Reorita (Universitas Jenderal Soedirman, 2012)
Calendar variation method is a technique that combines ARIMA modeling and regression modeling. Calendar variation is a cyclical pattern with varying periods due to the different calendar date position for each year. There are two types of calendar variation, trading day variation and holiday variation. In this research, modeling of time series with holiday variation was studied and modification of the modeling was developed for the case of holiday effect due to Eid’s day occur. The case study was conducted to the data of train passenger number at DAOP V Purwokerto. It was found that the last model for the underlying data was the regression model with the residual following seasonal ARIMA (1,1,1)(0,0,1)12 without constant parameter.